Antibodies to malondialdehyde-acetaldehyde modified low-density lipoprotein in patients with newly diagnosed inflammatory joint disease. (4th March 2021) - Kononoff, A; Hörkkö, S; Pussinen, P; Kautiainen, H; Elfving, P; Savolainen, E; Arstila, L; Niinisalo, H; Rutanen, J; Marjoniemi, O; Kaipiainen-Seppänen, O
Abstract : Objective :To assess antibodies to malondialdehyde–acetaldehyde-modified low-density lipoprotein (MAA-LDL) in patients with newly diagnosed inflammatory joint disease. Method : Patients with rheumatoid arthritis (RA), spondyloarthritis (SpA), and undifferentiated arthritis (UA), participating in the Northern Savo 2010 Study, were evaluated for metabolic syndrome (MetS), metabolic and inflammatory markers, antibodies to MAA-LDL, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis . Results : Among 135 newly diagnosed untreated patients, of whom 53 (39%) were diagnosed to have RA, 44 (33%) SpA, and 38 (28%) UA, 49%, 30%, and 47%, respectively, had MetS. After adjusting for age and gender, anti-MAA-LDL immunoglobulin (Ig)A (p = 0.009), IgG (p = 0.031), and IgM (p = 0.001) levels differed between the diagnostic categories, but not in patients with MetS present or absent. All antibody classes to MAA-LDL correlated with erythrocyte sedimentation rate (ESR), and IgA and IgG antibodies with high-sensitivity C-reactive protein (hs-CRP). IgA antibodies to MAA-LDL correlated with rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPAs), fasting plasma glucose, IgA antibodies to A. actinomycetemcomitans, and in IgA and IgG antibodies to P. gingivalis. Conclusion : Among various arthritis groups, antibodies to MAA-LDL were most common in RA. Antibodies to modified lipoproteins were associated with inflammation measured by ESR and hs-CRP. IgA antibodies to MAA-LDL correlated with age, antibodies to periodontal bacteria, RF, ACPA, and fasting glucose. Associations between antibodies to MAA-LDL and antibodies to periodontal bacteria, RA-associated antibodies, inflammatory parameters, and plasma glucose already reflect cardiovascular burden in inflammatory joint diseases at diagnosis.